2004
DOI: 10.1111/j.0007-0963.2004.05861.x
|View full text |Cite
|
Sign up to set email alerts
|

Refined localization of dyschromatosis symmetrica hereditaria gene to a 9.4-cM region at 1q21-22 and a literature review of 136 cases reported in China

Abstract: This study confirms linkage of DSH to a previously mapped region and refines the DSH gene to a 9.4-cM interval at 1q21-22. Likewise, the literature review indicates that DSH is not an uncommon disorder in China and the differences in the distribution of skin lesions could be related to race and environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 10 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…The genetic basis for each is still being worked out. An association has been found between DSH and the double-stranded RNA-specific adenosine deaminase (DSRAD) gene, [13][14][15][16][17][18][19][20] whereas loss-of-function in the keratin 5 (KRT5) gene and a gene locus mapping to chromosome 17p13. 3 have been described recently in cases of DDD.…”
mentioning
confidence: 99%
“…The genetic basis for each is still being worked out. An association has been found between DSH and the double-stranded RNA-specific adenosine deaminase (DSRAD) gene, [13][14][15][16][17][18][19][20] whereas loss-of-function in the keratin 5 (KRT5) gene and a gene locus mapping to chromosome 17p13. 3 have been described recently in cases of DDD.…”
mentioning
confidence: 99%
“…Cases with more widespread lesions involving the face, neck, and chest have been described 6. Our patient started to have skin lesions at a later age (10 years) when compared with most of the reported cases; late onset of DSH, however, has been reported in a few cases 10…”
Section: Discussionmentioning
confidence: 48%
“…Most reported cases of extracutaneous abnormalities are neurological abnormalities such as mental deterioration, dystonia, developmental regression, autistic disorder, depression, seizure disorder, intracranial hemangiomas, and Parry–Romberg syndrome 5,6,13. On the other hand, few cutaneous dermatoses have been reported with DSH-like psoriasis and neurofibromatosis type 1 7,14…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study 8,9 mapped the first locus for DSH on chromosome 1q11-1q21. The second locus was thought to be located at chromosome 6q24.2-6q25.2 by Xing et al, 10 but their patients showed dyschromatosis over almost their entire bodies, suggesting DUH.…”
Section: Discussionmentioning
confidence: 99%